Arendt’s Notion of Natality. An Attempt at Clarification (2017)
Arendt claims that our natality (i.e., our condition of being born) is the “source” or “root” of our capacity to begin (i.e., of our capacity to initiate something new). But she does not fully explain this claim. How does the capacity to begin derive from the condition of birth? That Arendt does not immediately and unambiguously provide an answer to this question can be seen in the fact that her notion of natality has received very different interpretations. In the present paper, I seek to clarify the notion. I bring together and examine Arendt’s scattered remarks about natality and propose a new interpretation that responds to the stated question. Along the way, I show how the various existing interpretations have arisen and argue that, in view of that question, they are inadequate.